Balancing the benefits and harms of thyroid cancer surveillance in survivors of Childhood, adolescent and young adult cancer: Recommendations from the international Late Effects of Childhood Cancer Guideline Harmonization Group in collaboration with the PanCareSurFup Consortium. (February 2018) - Clement, S.C.; Kremer, L.C.M.; Verburg, F.A.; Simmons, J.H.; Goldfarb, M.; Peeters, R.P.; Alexander, E.K.; Bardi, E.; Brignardello, E.; Constine, L.S.; Dinauer, C.A.; Drozd, V.M.; et al.
Highlights: We developed recommendations for DTC surveillance in CAYAC survivors. At-risk survivors should be counseled about options for DTC surveillance. It is recommended to use palpation or ultrasonography as a screening modality. Consultation with a thyroid specialist is recommended for survivors with a thyroid nodule. Abstract: Radiation exposure to the thyroid gland during treatment of childhood, adolescent and young adult cancer (CAYAC) may cause differentiated thyroid cancer (DTC). Surveillance recommendations for DTC vary considerably, causing uncertainty about optimum screening practices. The International Late Effects of Childhood Cancer Guideline Harmonization Group, in collaboration with the PanCareSurFup Consortium, developed consensus recommendations for thyroid cancer surveillance in CAYAC survivors. These recommendations were developed by an international multidisciplinary panel that included 33 experts in relevant medical specialties who used a consistent and transparent process. Recommendations were graded according to the strength of underlying evidence and potential benefit gained by early detection and appropriate management. Of the two available surveillance strategies, thyroid ultrasound and neck palpation, neither was shown to be superior. Consequently, a decision aid was formulated to guide the health care provider in counseling the survivor. The recommendations highlight the need for shared decision making regarding whether to undergo surveillance for DTC and in the choice of surveillance modality.